CSIG-13. TRPM7 INDUCES TUMORIGENESIS AND STEMNESS THROUGH NOTCH ACTIVATION IN GLIOMA. (9th November 2020) - Wan, Jingwei; Guo, Alyssa; Liu, Mingli
Abstract: Our group found that the inhibitory effect of TRPM7 on proliferation and invasion of human glioma cell is mediated by multiple mechanisms. TRPM7 regulates miR-28-5p expression, which suppresses cell proliferation and invasion in glioma cells by targeting Ras-related protein Rap1b. In particular, our group found that TRPM7 channels regulate glioma stem cell (GSC) growth/proliferation through STAT3 and Notch signaling. However, which Notch component(s) is crucial for its activity regulated by TRPM7, and its relationship with other GSC markers, such as CD133 and ALDH1, remain unclear. In the current project, we elucidate the mechanisms of TRMP7's regulation of Notch signaling pathway that contribute to the development and progression of glioma and maintenance of self-renewal and tumorigenicity of GSC using multiple glioma cell lines (GC) with different molecular subtypes and GSCs derived from the GC lines. 1) We first analyzed TRPM7 expression using the Oncomine database (https://www.oncomine.org ) and found that the TRPM7 mRNA expression is significantly increased in anaplastic astrocytoma, diffuse astrocytoma, and GBM patients compared to that in normal brain tissue controls. 2) TRPM7 is expressed in GBM, and its channel activity is correlated with Notch1 activation. Inhibition of TRPM7 downregulates Notch1 signaling, while upregulation of TRPM7 upregulates Notch1 signaling. 3) GSC markers, CD133 and ALDH1, are correlated with TRPM7 in GBM. 4) Targeting TRPM7 suppresses the growth and proliferation of glioma cells through G1/S arrests and apoptosis of glioma cells. 5) Targeting Notch1 suppresses the TRPM7-induced growth and proliferation of glioma cells, as well as the expression of GSC markers CD133 and ALDH1. In summary, TRPM7 is responsible for sustained Notch signaling activation, enhanced expression of GSC markers, and regulation of glioma stemness, which contribute to malignant glioma cell growth and invasion. Notch1 and ligand DII4 are key components that contribute GSC stemness.